Intellectual capital in Ugandan service firms as mediator of board governance and firm performance - Korutaro Nkundabanyanga, Stephen; Ntayi, Joseph M.; Ahiauzu, Augustine; Sejjaaka, Samuel K. (African Journal of Economic and Management Studies, 2014)
The purpose of this paper is to examine the mediating effect of intellectual capital on the relationship between board governance and perceived firm financial performance. Design/methodology/approach – This study was cross-sectional. Analyses were by SPSS and Analysis of Moment Structure on a sample of 128 firms. Findings – The mediated model provides support for the hypothesis that intellectual capital mediates the relationship between board governance and perceived firm performance. while the direct relationship between board governance and firm financial performance without the mediation effect of intellectual capital was found to be significant, this relationship becomes insignificant when mediation of intellectual capital is allowed. Thus, the entire effect does not only go through the main hypothesised predictor variable (board governance) but majorly also, through intellectual capital. Accordingly, the connection between board governance and firm financial performance is very much weakened by the presence of intellectual capital in the model – confirming that the presence of intellectual capital significantly acts as a conduit in the association between board governance and firm financial performance. Overall, 36 per cent of the variance in perceived firm performance is explained. the error variance being 64 per cent of perceived firm performance itself. Research limitations/implications – The authors surveyed directors or managers of firms and although the influence of common methods variance was minimal, the non-existence of common methods bias could not be guaranteed. Although the constructs have been defined as precisely as possible by drawing upon relevant literature and theory, the measurements used may not perfectly represent all the dimensions. For example board governance concept (used here as a behavioural concept) is very much in its infancy just as intellectual capital is. Similarly the authors have employed perceived firm financial performance as proxy for firm financial performance. The implication is that the constructs used/developed can realistically only be proxies for an underlying latent phenomenon that itself is not fully measureable. Practical implications – In considering the behavioural constructs of the board, a new integrative framework for board effectiveness is much needed as a starting point, followed by examining intellectual capital in firms whose mediating effect should formally be accounted for in the board governance – financial performance equation. Originality/value – Results add to the conceptual improvement in board governance studies and lend considerable support for the behavioural perspective in the study of boards and their firm performance improvement potential. Using qualitative factors for intellectual capital to predict the perceived firm financial performance, this study offers a unique dimension in understanding the causes of poor financial performance. It is always a sign of a maturing discipline (like corporate governance) to examine the role of a third variable in the relationship so as to make meaningful conclusions.
Keywords: Intellectual capital; Uganda; Mediation; Firm performance; Board governance